Rupture of the femoral component and severe metallosis of the knee 10 years after unicompartmental knee arthroplasty (UKA): a case report - Vecchini, Eugenio; Ditta, Alessandro; Gelmini, Margherita; Maluta, Tommaso; Valentini, Roberto; Ricci, Matteo; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2019)
A case of a 71-year-old man with femoral and tibial osteolysis and severe metallosis of the knee, resulting from abrasive wears of the metal components of a unicompartmental knee arthroplasty, that leaded to the rupture of the femoral component of the prosthesis is reported. An unicompartmental prosthesis, in a varus knee, was implanted in 2007. In March 2017, the patient felt that his knee was becoming increasingly unstable with pain and increasing disability. At clinical evaluation there was an effusion, 110° of flexion and – 10° of extension and a slight instability at the varus/valgus stress tests. BMI was 35. In a CT scan performed in June 2017 no signs of alteration were evident, but an X-Ray performed in January 2018 showed a rupture of the femoral component. A revision surgery was performed in February 2018. At the time of revision surgery, the synovitis and the metallosis were evident. A cemented total knee arthroplasty was performed. Samples of the fluid and surface did not show any bacterial growth. Histological examination confirmed the presence of a massive metallosis. The patient had a satisfactory rehabilitation. According to the literature, metallosis and rupture of the prosthetic components due to polyethylene wear after UKA is a common complication. In our case report the elevated BMI and varus knee accelerated the wear of the polyethylene. The aim of this case report is to enhance how an appropriate diagnosis (clinical and radiographic) and early treatment can lead to a successful result.